Neutrophilic granulocytes in the patients with burn injury - L. P. Pivovarov; I. V. Osipova; O. B. Ariskina; O. V. Orlova (Медицинская иммунология, 2023)
Severe burn injury (BI) is accompanied by disturbed microcirculation, water-electrolyte and acidbase imbalance within 2-3 days after the accident, and the development of toxemia within 4-12 days. The severity of toxemia depends on the area and depth of the lesion, resorption of tissue decay products, and development of a systemic inflammatory response syndrome. In the patients suffering with deep BI sepsis, it develops in 15% of cases. Pathogenesis of critical conditions is related to the functional activity of myeloid cells, including neutrophilic granulocytes (NG). Тhe determination of NG’s dysfunctions in patients with BI is important, both for prediction of septic complications and administration of rational therapy. The aim of our work was to study the functions of neutrophils in patients with severe BI and to determine early predictors of burn-associated sepsis. The study involved 53 patients with severe BI at the mean age of 43 years (32 to 52); the area of damage was 43% (17 to 63) of the body surface, with deep-burn area of 17 (13 to 27) %. The severity of BI was assessed using the Frank index, at the average value of 74 conventional units (62 to 89). Тwo groups of patients were identified: 24 persons without sepsis, and 29 people with sepsis and severe sepsis. The studies were carried out upon admission, on the 1st, 3rd, 5th, 10th , and 20th day of the burn disease. We determined the numbers of NGs expressing CD18+, CD14+, defensin+; serum contents of soluble defensins (sDеf), IL-6, IL-8 levels (ELISA); procalcitonin, as well as luminol-mediated spontaneous аnd induced NG chemiluminescence. Тhe results of this study showed a relationship between the amounts of NGs containing antimicrobial peptides, contents of NGs expressing CD18+ adhesion molecules, activation of oxidative metabolism, IL-6 overproduction, and development of sepsis in patients with burn injury, as well as with severity of burn trauma.